Condensed dewdrops self-ejecting on sprayable superhydrophobic CNT/SiO2 composite coating. Issue 44 (23rd May 2017) - Wang, Shanlin; Zhang, Jing; Yu, Xinquan; Zhang, Youfa
Abstract : We report a type of novel condensed dewdrops self-ejecting coating from sprayable paint, which was prepared by a self-assembly process of SiO2 nano-particles on hydroxylated carbon nano-tubes with subsequent chemical modification. Abstract : We report a type of novel condensed dewdrops self-ejecting coating from sprayable paint, which was prepared by a self-assembly process of SiO2 nano-particles on hydroxylated carbon nano-tubes with subsequent chemical modification. This work enlarges the application of sprayable superhydrophobic coatings for the enhancement of condensation heat transfer.